2015
DOI: 10.1088/0952-4746/35/3/727
|View full text |Cite
|
Sign up to set email alerts
|

Patient and staff dosimetry during radiographic procedures in an intensive care unit

Abstract: The performance of radiography in the Intensive Care Unit (ICU) may be associated with a certain level of radiation exposure for staff and patients in the unit. Little evidence on exposure levels is available in the literature. However, healthcare professionals in the ICUs at our centre tend to leave the room during radiographic examinations, potentially compromising patient care. The objectives of this study were to quantify dose levels within the ICU and to evaluate the performance of ICU x-ray studies accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Before the COVID‐19 pandemic, mobile imaging of regions other than the chest was relatively rare at the study sites (<6%). Other institutions have reported higher rates of up to 25% 38,39 …”
Section: Discussionmentioning
confidence: 93%
“…Before the COVID‐19 pandemic, mobile imaging of regions other than the chest was relatively rare at the study sites (<6%). Other institutions have reported higher rates of up to 25% 38,39 …”
Section: Discussionmentioning
confidence: 93%
“…In recent years, the use of portable X-rays has significantly increased by 1.7-fold due to COVID-19 [9]. This study, with other studies, commonly used thermoluminescent dosimeters (TLD) to estimate occupational doses [4,5,9]. These studies concluded that the average reported doses remained significantly lower than the annual occupational whole-body dose limit or lens dose limit of 20 mSv set by the International Commission on Radiological Protection (ICRP) [10].…”
Section: Introductionmentioning
confidence: 83%
“…Other than interventional radiology, scatter radiation may affect other parties in various settings. Scatter radiation from portable X-rays in wards could affect nearby patients and healthcare professionals [4,5]. While scatter radiation from pediatric X-rays may affect caregivers who help with the positioning of infants.…”
Section: Introductionmentioning
confidence: 99%
“…The reported uncertainty for the dose readings of these dosimeters is less than 7% with a lower limit of detectability of 0.1 mSv [24]. The TLD badges are worn under the lead apron at the chest height and are collected and read monthly.…”
Section: Staff Individual Monitoringmentioning
confidence: 99%